Testing and assessment of fatigue life prediction models for Indian PHWRs piping material under multi-axial load cycling. (April 2016) - Arora, Punit; Gupta, Suneel K.; Bhasin, V.; Singh, R.K.; Sivaprasad, S.; Tarafder, S.
Graphical abstract: Highlights: Axial–torsion fatigue tests were conducted on tube specimens of low C–Mn steel. Significant additional strain hardening under non-proportional loading condition. Cracking orientations measured and found dependent on loading condition. Fatigue life assessment using plastic strain energy density based scheme and ASME fatigue procedure. Abstract: In the present paper, experimental and analytical fatigue studies on primary piping material of Indian PHWRs, have been carried out under multi-axial loading with an aim to assess the adequacy of currently used fatigue life models based on ASME B&PV Sec-III procedure and plastic strain energy density. The experiments were conducted under axial, torsion and combined axial–torsion loading with different loading waveforms, phase angle and strain ratio (shear to axial). The tests under varying principal directions loading resulted in shorter fatigue lives. The orientations of crack initiation plane were measured and found dependent on the loading parameters which supports the idea of critical plane based fatigue models.